Promoting effective health communication: among vulnerable groups: a strategic approach (2016)
Health communication encompasses the study and use of communication strategies to inform and influence individuals and community decisions that enhance health. It links the domains of communication and health and is increasingly recognised and necessary element of efforts to improve personal and public health Vulnerable groups like people with one form of disability or the other, prisoners, internally displaced persons often have health needs demanding special attention than people that are not seemingly vulnerable. The paper explored how health communication can contribute to health promotion effort of health professionals individuals health seeking behaviour, individuals’ adherence to health messages and campaigns, the dissemination of health information to individuals and population. The paper examined the factors that could affect developing healthy benaviours and strategies to improve its. The paper concluded on the guidelines in developing messages to promote healthy behaviours.